Effects of PLGA nanofibre on osteoarthritic chondrocytes - B.S. Shamsul; Shiplu Roy Chowdhury; Ruszymah Haji Idrus; Nor Hamdan Mohamad Yahaya (Penerbit Universiti Kebangsaan Malaysia, 2018)
Chondrocytes obtained from osteoarthritis (OA) joints has been recognized as an abnormal cell; however, it’s proven to have potential in supporting cartilage regeneration. We have isolated chondrocytes from OA joints (OAC) and expanded chondrocytes growth medium (CGM). The growth kinetic, immunophenotyping and cell multilineage differentiation were analyzed to confirm the OAC stemness. The optimal condition to developed PLGA nanofibre with ratio 50:50 were 20% concentration of PLGA, flow rate with 0.3 mL/h, 10 kv voltage and 10 cm distance from nozzle to the collector. The toxicity level, scanning electron microscopy (SEM) and q-PCR analysis was performed in the present study. OAC fulfills the minimal criteria to be known to have stem cell as the cell easily adheres to the culture plate, shows high expression (≥95%) for CD13, CD29, CD44, CD73 and CD90 and less expression (≤2%) for CD45 and HLA-DR and potentially induced to mesodermal multilineage, which is osteocytes, adipocytes and chondrocytes. Toxicity test showed no adverse effect of PLGA towards the cell. Based on the cell-PLGA nanofibre interaction, difference in fibre size will influence the proliferation of the cell. Nanofibres with 100 nm in size showed high proliferation of OAC and better gene and protein expression compared to monolayer culture. Thus, we concluded that OAC has the potential to be used in cartilage regeneration based on the presence of stem cell markers as similar to the human bone marrow. The cartilage regeneration will be more efficient if OAC cultured on 3D microenvironment as showed in the present study.